CIVIL SERVICE PROGRAM OF HEALTH TEENAGER AND ACHIEVING TEENAGER IN LIMO VILLAGE, LIMO DISTRICT, DEPOK - Ritanti, Ritanti; Anggraini, Nourmayansa Vidya (Institut Seni Indonesia Padangpanjang, 2019)
Limo Village is one of the villages located in Limo District, Depok City, West Java Province. This region is located in an urban area with an area of 12.12 km2 and a population of 110,275 men and women (bps, 2016). The results of preliminary studies on partners obtained data that the planning program for individual teenagers in Limo Village is currently not optimal; lack of information, knowledge and understanding related to health planning; most people do not yet have the awareness to participate in planning in the future; low skills / life skills of teenagers in improving life planning. Various impacts arising are that teenagers do not have a plan in their lives, both short-term and long-term plans so that youth activities run aimlessly and have an impact on teenagers health problems. The low level of teenagers planning also affects teenagers in carrying out daily activities. The purpose of this community service activity is to increase the knowledge and skills of teenagers in making life planning so that everyday youth activities are more focused, especially planning on health problems. The conclusion of this activity is an increase in knowledge and skills in teenagers in making life planning, both short-term and long-term goals.